Cadmium absorption and translocation of amaranth (Amaranthus mangostanus L.) affected by iron deficiency. (January 2020) - Zou, Rong; Wang, Li; Li, Yuncong C.; Tong, Zhaohui; Huo, Wenmin; Chi, Keyu; Fan, Hongli
Abstract: Amaranth ( Amaranthus mangostanus L.) has superior capability for accumulating cadmium (Cd) and has the potential to be used for phytoremediation of Cd contaminated soils. Iron (Fe) is chemically similar to Cd and may mediate Cd-induced physiological or metabolic impacts in plants. The purpose was to investigate the model of time-dependent and concentration-dependent kinetics of Cd absorption under Fe deficiency, understanding the physiological mechanism of Cd absorption in amaranth roots. The kinetic characteristics of Cd uptake by amaranth grown in Cd enriched nutritional solution with or without Fe addition and with methanol-chloroform, carbonyl cyanide 3-chlorophenylhydrazone (CCCP), and lanthanum chloride (LaCl3 ) were compared using 109 Cd 2+ isotope labeling technique. The results showed that Cd uptake was time-dependent and about 90–93% of uptake occurred during the first 150 min. The kinetics of Cd uptake showed that two stages were involved. The saturation stage fitted the Michaelis-Menten model when concentrations of Cd were lower than 12.71 μmol/L and then the absorption of Cd by roots was increased linearly during the second stage. Only linear absorption was observed with methanol-chloroform treatment while the metabolic inhibitor CCCP inhibited only the saturation absorption process, and the Ca channel inhibitor LaCl3 partially inhibited the two stages of absorption. These results indicated that the root absorption of 109 Cd 2+ was enhanced under Fe deficiency which induced more Fe transporters in the root cell membrane, and the Ca channel, apoplastic and symplastic pathways enhanced the Cd absorption in roots. Graphical abstract: Image 1 Highlights: A Michaelis-Menten kinetic model was described 109 Cd 2+ uptake in amaranth. The root absorption of 109 Cd 2+ was enhanced under Fe deficiency. La 3+ inhibited the saturation and linear absorption process of 109 Cd 2+ in roots. CCCP only inhibited the saturation absorption process of 109 Cd 2+ in roots. Abstract : The absorption of 109 Cd 2+ in amaranth roots was enhanced under Fe deficiency, which was described with the Michaelis-Menten kinetic model.